Uji Daya Hambat Ekstrak Etanol Daun Binahong (Anredera cordifolia (Ten) Steenis) terhadap Propionibacterium acnes - Waris, Muhammad Anugerah Alam; A.S., Indarto (NUTRITURE JOURNAL; Vol 2 No 3 (2023): Nutriture Journal, 2023)
Background : Binahong (A. cordifolia) contains flavonoids, alkaloids, oleanolic acid, protein, ascorbic acid and saponins which have antibacterial activity. Objective : To determine the antibacterial activity of Binahong (A. cordifolia) leaves against Propionibacterium acnes. Method : Binahong (A. cordifolia) leaf extract obtained by the maceration method using 96% ethanol was then made in three concentrations, namely 5% w/v, 10% w/v, 15% w/v and negative control. Testing of the antibacterial activity of Binahong (A. cordifolia) leaf extract was carried out using the disk diffusion method. Observations were made after 24 hours and then the inhibition zone that appeared was measured. Results : Binahong (A. cordifolia) leaf extract with concentrations of 5%, 10% and 15% showed inhibition zones against P. acnes of 12 mm, 18.66 mm and 25.66 mm respectively. Conclusion : Based on the tests that have been carried out, it can be concluded that the ethanol extract of Binahong leaves (A. cordifolia) has antibacterial compounds against P. acnes